Source identification problems for the wave equation on graphs. (September 2015) - Avdonin, Sergei; Nicaise, Serge
Abstract We consider source identification problems for the wave equation on graphs. The main advantage of our approach is its locality. Our algorithm reduces essentially to the resolution of linear integral Volterra equations of the second kind and is new even for an interval.